2016
DOI: 10.1111/aos.13113
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic characteristics of retinal detachment surgery at a specialized unit in Denmark

Abstract: ABSTRACT.Purpose: To examine the incidence of retinal detachments and to evaluate patient profiles and surgical characteristics. Methods: Retrospective review of patients operated for primary retinal detachment (RD) and redetachment between 2010 and 2012 at the Department of Ophthalmology, Odense University Hospital, Denmark. We included all RD such as rhegmatogenous retinal detachment (RRD), tractional retinal detachment (TRD) and exudative retinal detachment (ERD). Results: In total, 779 RD surgeries were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 46 publications
6
39
1
7
Order By: Relevance
“…Rates of RRD patients undergoing vitrectomy have shown a more than 10-fold increase from 1985 to 2004 in UK (El-Amir et al 2009), and in our centre, vitrectomy has become the preferred surgical technique for primary RRD (Sahanne et al 2017), being in line with other latest studies (Poulsen et al 2016;Haugstad et al 2017). In our study, the RRD eyes operated with conventional SB surgery without vitrectomy were not included or analysed.…”
Section: Discussionsupporting
confidence: 54%
“…Rates of RRD patients undergoing vitrectomy have shown a more than 10-fold increase from 1985 to 2004 in UK (El-Amir et al 2009), and in our centre, vitrectomy has become the preferred surgical technique for primary RRD (Sahanne et al 2017), being in line with other latest studies (Poulsen et al 2016;Haugstad et al 2017). In our study, the RRD eyes operated with conventional SB surgery without vitrectomy were not included or analysed.…”
Section: Discussionsupporting
confidence: 54%
“…; Poulsen et al. ) have been reported. Hajari, in his longitudinal study over 10.5 years, found rising incidences over time with the highest incidence of approximately 17.0/100 000 in 2011.…”
Section: Discussionmentioning
confidence: 92%
“…An incidence of 18.2/100 000 was found in the Netherlands (Van de Put et al 2013). In studies from other Nordic countries, incidence rates of 6.9/100 000 in Finland (Laatikainen et al 1985), 10.6/ 100 000 in Sweden (Algvere et al 1999) and 13.7/100 000 and 20.0/ 100 000, respectively, in Denmark (Hajari et al 2014;Poulsen et al 2016) have been reported. Hajari, in his longitudinal study over 10.5 years, found rising incidences over time with the highest incidence of approximately 17.0/100 000 in 2011.…”
Section: Discussionmentioning
confidence: 95%
“…Primary rhegmatogenous retinal detachment (RRD) is the most common type of retinal detachment and is an acute vision-threatening disease in ophthalmology [1]. Scleral buckling (SB) had been the leading approach since introduced by Schepens et al [2] in the 1950s until the 1980s with the advancement of pars plana vitrectomy [3].…”
Section: Introductionmentioning
confidence: 99%